Interspeech 2019 2019
DOI: 10.21437/interspeech.2019-1541
|View full text |Cite
|
Sign up to set email alerts
|

ReMASC: Realistic Replay Attack Corpus for Voice Controlled Systems

Abstract: This paper introduces a new database of voice recordings with the goal of supporting research on vulnerabilities and protection of voice-controlled systems (VCSs). In contrast to prior efforts, the proposed database contains both genuine voice commands and replayed recordings of such commands, collected in realistic VCSs usage scenarios and using modern voice assistant development kits. Specifically, the database contains recordings from four systems (each with a different microphone array) in a variety of env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…Due to its implementation simplicity, score fusion is the most commonly used fusion method in multibiometric systems [98]. However, recent works [32,55] have shown that the scored fusion outperformed feature fusion as a fused feature is more complex and may lose its significant traits, which can be used to distinguish accurately between different speaking individual [55].…”
Section: Searching Speaker Modelmentioning
confidence: 99%
“…Due to its implementation simplicity, score fusion is the most commonly used fusion method in multibiometric systems [98]. However, recent works [32,55] have shown that the scored fusion outperformed feature fusion as a fused feature is more complex and may lose its significant traits, which can be used to distinguish accurately between different speaking individual [55].…”
Section: Searching Speaker Modelmentioning
confidence: 99%
“…In this work, publicly available ReMASC dataset is used which aims to develop effective countermeasures against replay spoofing attack on VAs [5]. The details of the dataset collection strategies can be found in [5]. The details of the data partition for the experiments in this paper are available in [19].…”
Section: Dataset Feature Set and Classifiersmentioning
confidence: 99%
“…Among the various spoofing attacks, replay attack is becoming major concern for the community as it is easy to mount, but difficult to detect. Although, the design of countermeasure (CM) systems for ASV and VAs looks similar, there are important differences in anti-spoofing strategies for these systems, which are explained in [5]. Considering these differences, recently, Realistic Replay Attack Microphone Array Speech Corpus (ReMASC) has been released, which is specifically designed to develop countermeasures against replay spoofing attack on VAs [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ReMASC (Realistic Replay Attack Microphone Array Speech Corpus) is the first publicly available database that is designed specifically for the protection of voice-controlled systems (VCSs) against various replay attacks in various conditions and environments [84]. The ASVspoof 2019 challenge consists of simulated data for clear theoretical analysis of audio spoofing attacks in physical environments, however, it brings a simulation-to-reality gap.…”
Section: E) Remascmentioning
confidence: 99%